An analytical Study of the standard of Syrian Citizen's living (Reality & Prospects during the period from 2010 up to 2019). (Latakia University Journal - Economic and Legal Sciences Series, 2020)
The search deals with an analytical Study  of the Standard  of living  of the Syrian Citizens .First , the Research  aims  to study  the Standard of living  for the period  before the war on Syria which extended  between years  2000-2010 .  Then it deals with  the living standard after year 2011 through the study of  several indications   such as : cost of living , income distribution , family budget  and analysis the reasons that led to the deterioration of the standard of living either those relating to the circumstances of war  as the  loss the government of the most  important of financial resources represents in the petroleum Wells ,  or those related to the exchange rate . The research also aims to analyze and evaluation of the Government measures to face the deterioration from two points of view; one believes the success of the government giving its supports, other believes the fail of the government giving its supports too.Also , the Search   aims   to study  the social  reflection  of the low standard  of living  related  to increase of  crime rates or the low level  of education .Finally, the study  provided  a set of  proposals that help in improving the standard of living, some of them  are related  to the mechanism of meeting the needs of the Syrian citizen from the basic provisions , while others related to the mechanism of managing the  monetary market and exchange .The Search depended upon the  Statistical analysis systematic in the study.The Study reached to set of results the most of connected to the low of the actual monetary income with about 88% and the low of living level by which 85% of people under the level of poverty and this due to several reasons some of which related the Exchange rate and others related the government failure to control the prices.